ANALISIS PENGARUH KECUKUPAN MODAL TERHADAP BIAYA INTERMEDIASI DAN PENGAMBILAN RISIKO BANK (Studi Kasus pada Bank Umum yang Terdaftar di Bursa Efek Indonesia Periode 2013-2017) - Rosa Yuni Rahmawati; Agus Purwanto (Diponegoro Journal of Accounting, 2019)
This study aims to examine the effect of capital adequacy on intermediation cost and bank risk taking. Capital adequacy is measured using the Capital Adequacy Ratio (CAR), the ratio of total equity to total assets (RETTA), and capital dummy. Intermediation costs are measured using Net Interest Margin (NIM) 1 and NIM 2. Control variables in this study are management efficiency, revenue diversification, risk-weighted assets to total assets, statutory reserve, and financial intermediation.            The population in this study consisted of banks in Indonesia, especially banks listed on the Indonesia Stock Exchange for the period 2013-2017. Sample determined with purposive sampling method. The total sample is 161 banks.            This study used multiple regression analysis to test hypotheses. The results of this study indicate that capital adequacy (CAR and RETTA) has a positive effect on intermediation costs (NIM1 and NIM2), capital adequacy (CAR and RETTA) have a negative effect on risk taking, and capital adequacy (capital dummy) has no effect on intermediation costs (NIM1 and NIM2) and risk taking.